The pulvinus endodermal cells and their relation to leaf movement in legumes of the Brazilian cerrado - Rodrigues, T. M.; Machado, S. R. (Georg Thieme Verlag Kg, 2007)
Legume pulvini have a clearly delimited endodermis, whose variable content has been associated with the velocity and type of leaf movement: pulvini in leaves with fast nastic movement contain starch grains; pulvini in leaves with slow nastic movements have calcium oxalate crystals as well as starch grains in the endodermis. However, the studies carried out to date have involved few legume species. This study therefore purported to examine the consistency of this hypothesis in other legumes. Thus, the structure and content of the pulvinus endodermal cells of nine legumes of the Brazilian cerrado, with different types and velocities of leaf movement, were investigated: slow nyctinastic and heliotropic movements (Bauhinia rufa, Copaifera langsdorffii, Senna rugosa - Caesalpinioideae; Andira humilis and Dalbergia miscolobium - Faboideae; Stryphnodendron polyphyllum - Mimosoideae), slow heliotropic movement (Zornia diphylla - Faboideae), and fast seismonastic and slow nyctinastic and heliotropic movements (Mimosa rixosa and Mimosa flexuosa - Mimosoideae). Samples were prepared following standard plant anatomy and ultrastructure techniques. The endodermis of all the species contains starch grains. In the species displaying only slow movements, calcium oxalate prismatic crystals were observed in addition to starch grains, except in Zornia diphylla. in conclusion, oxalate crystals occur only in endodermal cells of pulvini that display slow movements, while starch grains are always present in pulvinus endodermal cells of plants with any kind of movement.
Keywords: crystals; endodermis; gravity; leaf movements; pulvinus; starch grains; structure